2004
DOI: 10.1177/0091270004268320
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Ibuprofen Enantiomers in Very Premature Neonates

Abstract: The objective of the present study was to evaluate the pharmacokinetic parameters for both S- and R-ibuprofen enantiomers in very premature neonates (gestational age strictly inferior to 28 weeks) and possible relationships between the pharmacokinetic parameters and various covariates. Newborns were randomized to receive ibuprofen or placebo for the prophylactic treatment of patent ductus arteriosus (PDA) at an initial dose of 10 mg/kg ibuprofen within 6 hours after birth, followed by two 5-mg/kg doses at 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…Histograms of AUC(0,24 h) as a function of treatment success Table 4 Probability of success in the 66 000 simulated neonates greater increase as compared with other subfamilies.These important maturational effects could explain the significant increase in ibuprofen clearance with postnatal age. Age has already been shown to be related to the increase in ibuprofen clearance; however, Gregoire et al [8] found gestational age whereas Van Overmeire et al [6] and Aranda et al [5] found postnatal age. In our final model, postnatal age had a much more important effect on clearance (P < 10 -4 ) than gestational age.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…Histograms of AUC(0,24 h) as a function of treatment success Table 4 Probability of success in the 66 000 simulated neonates greater increase as compared with other subfamilies.These important maturational effects could explain the significant increase in ibuprofen clearance with postnatal age. Age has already been shown to be related to the increase in ibuprofen clearance; however, Gregoire et al [8] found gestational age whereas Van Overmeire et al [6] and Aranda et al [5] found postnatal age. In our final model, postnatal age had a much more important effect on clearance (P < 10 -4 ) than gestational age.…”
Section: Figurementioning
confidence: 97%
“…Ibuprofen is a nonselective nonsteroidal antiinflammatory agent that induces closure of the patent ductus arteriosus by inhibiting cyclo-oxygenase [3,4]. So far, few studies of ibuprofen pharmacokinetics have been performed, and only in small groups of premature infants [5][6][7][8], showing a very large variability in drug pharmacokinetic parameters.The aim of the present study was to characterize ibuprofen pharmacokinetics more extensively in a larger group of neonates and to optimize an individualized dosage schedule in neonates of variable gestational and postnatal age suffering from PDA. This was achieved by (i) developing a population pharmacokinetic model to describe the mean ibuprofen pharmacokinetics, (ii) using a pharmacostatistic model to identify infant characteristics that could influence the pharmacokinetics, the intersubject and residual variabilities and (iii) investigating relationships between AUC and ibuprofen efficacy and side-effects for PDA closure.The most relevant toleration parameter for ibuprofen is known to be potential renal toxicity, so in the study, renal side-effects were assessed using creatinine clearance and urine output.…”
Section: Introductionmentioning
confidence: 99%
“…R-ibuprofen and S-ibuprofen half-lives were about 10 h, and 25.5 h, respectively. The mean clearance of R-ibuprofen (12.7 mL/h) was about 2.5-fold higher than for S-ibuprofen (5.0 mL/h) [26]. The lower clearance and longer half-life of S-ibuprofen suggests that pharmacokinetic predictions based on racemic assays may underestimate the duration of pharmacologic effect.…”
Section: Pharmacokineticsmentioning
confidence: 86%
“…The population PK models (see Supplementary File 1) were compared with respect to birth weight, gestational age (GA), and postnatal age (PNA) of the cohort, ibuprofen-dosing regimen, route of administration, and studied ibuprofen enantiomers [12, 22, 23, 30, 31]. …”
Section: Methodsmentioning
confidence: 99%